Transport phenomena fundamentals - Plawsky, Joel L., 1957- (Chemical industries., 2019)
"The Fourth edition of Transport Phenomena Fundamentals continues with its streamlined approach to the subject of transport phenomena, based on a unified treatment of heat, mass, and momentum transport using a balance equation approach"--